Performance-Based Design in Structural Fire Engineering - Youssef, Maged A. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The performance-based design of structures in fire is gaining growing interest as a rational alternative to the traditionally adopted prescriptive code approach. This interest has led to its introduction in different codes and standards around the world. Although engineers widely use performance-based methods to design structural components in earthquake engineering, the adoption of such methods in fire engineering is still very limited. This Special Issue addresses this shortcoming by providing engineers with the needed knowledge and recent research activities addressing performance-based design in structural fire engineering, including the use of hotspot analysis to estimate the magnitude of risk to people and property in urban areas; simulations of the evacuation of large crowds; and the identification of fire effects on concrete, steel, and special structures.